Perbedaan Experienced Workplace Incivility Ditinjau Dari Status Pegawai Dan Jenis Kelamin Pada Tenaga Kependidikan - Nova Yulia Mayang Citra; Nadhirotul Laily; Ima Fitri Sholichah (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research was to examine the difference between experienced workplace incivility based on the status of employe and gender. Quantitative method used in this research. The population in this study were the employee of X University with saturated sampling technique, the total respondents of 52 employees (25 jobhoders and 27 contract employees; 19 man and 33 woman). The instrument used was the experienced workplace incivility scale consisting of 7 items. Data analysis in this research used independent sample t-test. This study found that the hypothesis was rejected (p > 0.05), so there is no difference in experienced workplace incivility based on the status of employee and gender. This research findings extend past research on wokplace incivility especially for educational staff in university.